Penguatan Kemampuan Ibu Rumah Tangga Berbasis Tanaman Herbal dalam mewujudkan Dokter Keluarga - Nurmawati, Thatit Nurmawati (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
Health is always sought for survival. Herbal plants are an alternative therapeutic treatment for maintaining health. Housewives who are members of the PKK in Mojorejo village are partners in this activity. The aim of the activity is to increase knowledge and improve skills to process herbas plants into family medicine in creating a healthy village based on herbal plants. The method used to solve partner problems is counseling and direct practice by partners. The results of the service showed a change in the level of partner knowledge from 15.04 to 41.96. The Mann Whitney test shows that there is an effect of counseling on knowledge (p 0.00). Independently, partners are skilled at processing herbal plants to overcome their health problems. Skills and knowledge are important to support healthy villages based on herbal plantsAbstract written in English.